2020
DOI: 10.1111/jar.12803
|View full text |Cite
|
Sign up to set email alerts
|

Looking back, looking forward: Methodological challenges and future directions in research on persons with profound intellectual and multiple disabilities

Abstract: Background: Within the context of the Special Interest Research Group (SIRG) on Persons with Profound Intellectual and Multiple Disabilities (PIMD), researchers often discuss the methodological problems and challenges they are confronted with. The aim of the current article was to give an overview of these challenges. Methods: The challenges are centred on six topics. These reflect the main components of a study's design: (a) participant demarcation, (b) participant recruitment, (c) data collection and instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(88 citation statements)
references
References 87 publications
(154 reference statements)
4
72
0
Order By: Relevance
“…Several limitations of the present study should be acknowledged. First, the small samples due to the low prevalence rates, the vulnerable health conditions [ 2 , 51 ], and accessibility to EGAT of our target group affect generalizability. The results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several limitations of the present study should be acknowledged. First, the small samples due to the low prevalence rates, the vulnerable health conditions [ 2 , 51 ], and accessibility to EGAT of our target group affect generalizability. The results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The momentary observations based on videos might not be fully representative of the dyadic communicative interactions across various daily activities. Researchers could consider a combination of different methodologies to strengthen the research findings [ 51 ], for instance, integrating interviews with proxies to triangulate quantitative data and provide a comprehensive picture of the dyadic communicative interactions in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…The CPADULT, as is the CPCHILD, focusses on observation of practical everyday activities and behaviour. Although, interpretation of behaviour can also be biased by the observers (Maes, 2020 ) because of their own knowledge of the individual and previous experiences with the individual in similar situations (Munde et al, 2011 ). When validating the Dutch version of the CPCHILD we assessed the inter‐observer reliability in asking two members of the family—mostly mother and father—to complete the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Another identified challenge involves the lack of validated research instruments (e.g. evaluated for their psychometric properties) to assess this group of participants (Maes et al 2021, Engelhardt et al 2020. This is also reflected in this review.…”
Section: Limitations Future Directions and Implications For Practicementioning
confidence: 99%
“…Since it is often very difficult to assess the exact degree of intellectual disability in children with severe to profound ID (i.e. IQ < 20), who also have several other disabilities (Nakken and Vlaskamp 2007, Maes et al 2021, Rensfeldt Flink et al 2020, children reported to have a severe intellectual disability are also often included in studies of PIMD (Arthur-Kelly et al 2018, Bindels-de Heus et al 2013. By definition, adaptive difficulties are characteristic features in ID in general (ICD-11, World Health Organization, 2018).…”
Section: Introductionmentioning
confidence: 99%